Attention Deficit Hyperactivity Disorder (ADHD) Student Facts - Sesrita, Afridha; Asep Supena; Totok Bintoro (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The study aimed to analyze facts related to ADHD students through international publication trends based on the Scopus database with publishers Springer, Taylor, Elsevier, and Hindawi. This study used a systematic literature review method with a qualitative approach. Studies have shown a gap between knowledge of early warning signs of ADHD and effective preventive interventions. Early interventions, such as behavioral training, are effective in reducing ADHD symptoms and improving some aspects of executive function. In addition, exposure to psychosocial stress, nutritional stress, immunological stress, and organic pollutants during early development may increase the risk of ADHD. Several treatment strategies, including the use of psychostimulants and psychosocial interventions, are effective in reducing ADHD symptoms. Factors such as age, disorder severity, and underlying health conditions should be considered when selecting a treatment, with periodic evaluations to monitor response to treatment and possible side effects.